A Case of Enteropathy Associated T-Cell Lymphoma (EATL) with Aberrant Phenotype, CD8+, CD56+: From Diagnosis to Death. (28th October 2020) - Clarke-Brodber, A; Eldibany, M; Victor, T
Abstract: Introduction/Objective: Enteropathy Associated T-Cell Lymphoma (EATL) is a rare and aggressive subtype of primary intestinal T cell lymphoma which occurs in patients with Celiac Disease (CD), most prevalent in the western world with an incidence rate of 0.22-1.9 cases per 100, 000. The classic immophenotype of these neoplastic intestinal T cells show loss of CD8 and CD56. The adherence to gluten-free diet, markedly decreases the incidence of this complication. Methods: The patient's previous and current biopsies, autopsy and EMR were reviewed. The patient is 66-year female that was diagnosed with Celiac Disease in 2003 after duodenal biopsy showed features suggestive of CD with positive anti-endomysial IgA antibody serology. She presents currently with burning abdominal pain, with subsequent CT scan showing a mass in the small bowel with mid gut rotation and lesions in the lungs, liver and bladder. Endoscopy showed multiple lesions extending from the hypopharynx to the large bowel, which on biopsy showed CD3+ lymphocytes expanding the lamina propria and infiltrating the crypt epithelium. Given the patient's clinical history a diagnosis of EATL was made. The patient passed 5 days after diagnosis due to small bowel perforation. Results: The initial duodenal biopsy showed villous blunting and increased intraepithelial lymphocytes. The biopsies of the gastrointestinal lesions show abnormal infiltrate of pleomorphic, intermediate in size lymphocytes with round to irregular and occasionally cleaved nuclei with pale to clear cytoplasm. These cells infiltrate the crypt epithelium. The immophenotype of these neoplastic cells are positive for CD3, CD7, CD8, CD56, TIA-1 and BF1, while negative for CD4, CD5 and CD30. T cell clonality was also positive. In addition to the above lesions, autopsy revealed involvement of an area of small bowel perforation with full-thickness mucosal wall involvement by the neoplastic cells. In addition, there is widely dissemenated disease involving the lung, liver, bone marrow, spleen, mesenteric lymph nodes, omentum, bladder, ovaries and myometrium (first report of uterine involvement). Conclusion: CD8 positive EATL may occur in 19-30% of cases, and increases up to 50% in refractory CD. The differential diagnosis of MEITL, which is typically CD8 positive, is important and most be distinguished on the basis of clinical setting in the presence of Celiac Disease.